The Regulation of the Hippo Pathway by Intercellular Junction Proteins - Usama Sharif Ahmad; Jutamas Uttagomol; Hong Wan (Life, 2022)
The Hippo pathway is an evolutionarily conserved pathway that serves to promote cell death and differentiation while inhibiting cellular proliferation across species. The downstream effectors of this pathway, yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ), are considered vital in promoting the output of the Hippo pathway, with activation of upstream kinases negatively regulating YAP/TAZ activity. The upstream regulation of the Hippo pathway is not entirely understood on a molecular level. However, several studies have shown that numerous cellular and non-cellular mechanisms such as cell polarity, contact inhibition, soluble factors, mechanical forces, and metabolism can convey external stimuli to the intracellular kinase cascade, promoting the activation of key components of the Hippo pathway and therefore regulating the subcellular localisation and protein activity of YAP/TAZ. This review will summarise what we have learnt about the role of intercellular junction-associated proteins in the activation of this pathway, including adherens junctions and tight junctions, and in particular our latest findings about the desmosomal components, including desmoglein-3 (DSG3), in the regulation of YAP signalling, phosphorylation, and subcellular translocation.